Thermodynamics of the pseudogap in cuprates - Tallon, Jeffery L.; Storey, James G. (Frontiers in Physics, 2022)
The key thermodynamic characteristics of the pseudogap state in cuprate superconductors are reviewed. These include YBa_2Cu_3O_7-δ, Y_0.8Ca_0.2Ba_2Cu_3O_7-δ, YBa_2Cu_4O_8, Bi_2Sr_2CaCu_2O_8+δ, La_2-xSr_xCuO_4 and Tl_2Ba_2CuO_4. The electronic specific heat was extracted using a differential technique and the evolution of the specific heat coefficient γ and electronic entropy, S, as a function of temperature, doping and magnetic field reveals a canonical behaviour summarised by the following. The normal-state gap which opens in the pseudogap domain apparently remains open to the highest temperatures investigated. The gap decreases in magnitude with increasing doping and closes abruptly at a critical doping of p ≈ 0.19 holes/Cu, independent of temperature. In this picture T^*(p), above which the pseudogap opens, is a vertical line similar to the vertical line separating incoherent and coherent antinodal quasiparticle states found in ARPES. The important role of fluctuations is evident by a diverging enhancement of γ(T) either side of T_c and this enables extraction of the mean-field transition temperature T_c^mf > T_c, defining a crescent of parapairing above T_c(p) which extends across the entire superconducting phase diagram and which is quite distinct from pseudogap phenomenology. The data is consistent with d-wave pairing and the BCS ratios are extracted, revealing canonical near-weak-coupling behaviour across the overdoped region with a sudden suppression occurring at p ≈ 0.19 when the pseudogap sets in.